Plan de intervención primaria en adolescentes entre 14-16 años. Relación entre características de personalidad y riesgo de trastornos de la conducta alimentaria del Centro Educativo Cordillera de la ciudad de Loja de agosto 2013 a febrero de 2014 - Veintimilla Vega, Georgina Alexandra (2015)
The eating behavior disorders (TCA), Anorexia nervosa (AN) and Bulimia nervosa (BN), are complex psychosomatic disturbances of multifactorial origin, intervened by sociocultural determinants, closely related to changes in routines and eating lifestyles, with aesthetic/body ideals, manifested particularly in the adolescent population. For this reason the present investigation aims to perform a primary intervention Plan in adolescents at risk for disorders of eating behavior, the same he moves to prevent the emergence of new cases of TCA and to create and strengthen adolescent protection factors. To achieve this goal initially the risk was assessed to present acts through the inventory of eating behavior disorders EDI, later personality characteristics was determined by average IPDE personality questionnaire. The research work was conducted with 32 youth aged 14-16, of the educational center of the city of Loja, themselves presenting risk for TCA, as personality characteristics featured in this population are avoiding traits with a 53%; dependent with 28%, obsessive compulsive with 10%, the feature limit with paranoid with 3% and 6%. These results suggest that personality could be closely linked to the home either AN or BN, that are closely related to the types of personalities present in the population that has already developed an eating disorder. Key words: Adolescence, Prevention, IPDE, EDI